Assessment of a mortar with recycled aggregate from a concrete improved by carbonation: a look to a sustainable construction (2019)
In this article, some of the physical, mechanical, and durability properties of mortars were evaluated. These mortars had partial replacements of the natural fine aggregate (NFA) with recycled fine aggregate (RFA) and carbonated recycled fine aggregate (CRFA) in amounts of 0%, 25%, and 50%. For this purpose, 3 groups of mortar mixtures were elaborated with a w/c ratio of 0.65. The results showed that an increase in the percentage of replacement of the CRFA, led to an improvement in the compressive strength of the mortar, as well as a lower superficial absorption rate.